Game theory framework applied to wireless communication networks - Yang, Chungang; Li, Jiandong (IGI Global, 2016)
This book is a pivotal reference source for the latest scholarly research on the application of game-theoretic approaches to enhance wireless networking, and features prevailing coverage on a range of topics relating to the advanced game model, mechanism designs, and effective equilibrium concepts.